Peran Orang Tua Dalam Menyelesaikan Problem Remaja pada Novel Dua Garis Biru Karya Lucia Priandarini - Gelaugina diva nur hidayah; Prastya wati candra kartika; Eva dwi kurniawan (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research focuses on how parents play a role in helping teenagers solve their problems. The purpose of this research is to find out the handling efforts made by parents in overcoming teenage problems in the novel two blue lines by Lucia Priandarini. The research method used in this study uses a qualitative descriptive method with a hermeneutic approach. The results of this study show that the problem of teenagers in this two blue lines novel is early marriage caused by premarital free sex behavior. The role of parents in helping to overcome adolescent problems in this novel is by parents as supervisors as well as counselors, by establishing communication between parents and children so that good relationships are formed to help solve problems that occur.